MORAL CONFLICTS OF ORGAN DONATION IN NICK CASSAVETES' MYSISTER'S KEEPER MOVIE (2009): A PSYCHOANALYTIC APPROACH - SEPTININGTYAS, DEWI NINA (2011)
This study investigates moral conflicts of organ donation reflected in My Sister's Keeper movie viewed from psychological approach. This research is aimed to analyze moral conflicts of organ donation viewed in terms of moral based on psychoanalytic perspective and analyze the movie based on its structural elements. In achieving the objectives, the researcher uses descriptive qualitative method as the type of the research. The object of this study is My Sister's Keeper movie by Nick Cassavetes. The data sources are the primary data and secondary data. The primary data is the movie itself and the secondary data are the other data which have relationship with the study, such as some biography of the author, the articles from internet, the books and other relevant information. In collecting the data, the researcher uses library research and documentation method, and the technique of the data analysis is descriptive analysis. This research consists of two conclusions. Firstly, based on the structural analysis, it is apparent that in this movie, Nick Cassavetes conveys a moral message that human body is something borrowed, but the owner also has the right to keep and maintain the integrity of their organs in order to survive. Secondly, based on the psychoanalytic analysis, it is evident that in this movie, the director illustrates a psychological phenomenon of moral conflicts because of the different perspectives.